Oral health-related quality of life of edentulous patients after complete dentures relining - Krunić, Nebojša; Kostić, Milena; Petrović, Milica; Igić, Marko (Vojnosanitetski pregled, 2015)
Background/Aim. Tooth loss affects oral health-related life quality. More than a third of edentulous patients are not fully satisfied with their complete dentures and mainly complain of insufficient stability, retention, and pain during mastication. Solving the problem may include relining by materials that are based on silicone or acrylic. The aim of this study was to determine the level of patients’ satisfaction before and after relining upper dentures with soft and rigid liners. Methods. The patients (n = 24) were divided into two study groups. Maxillary denture relining of the first group of patients was performed with hard acrylic based resins while in the second group of patients complete denture was relined with a silicone-based soft liner. They were asked the questions from the specifically adapted the Oral Health Impact Profile Questionnaire for edentulous patients before and three months after relining dentures. Results. After relining the patients showed a higher degree of satisfaction with their dentures in all the tested domains (masticatory function, psychological discomfort, social disability and retention and hygiene). The patients with soft denture relines were more satisfied. Conclusion. Relining of maxillary complete dentures significantly positively impacts the quality of life of patients in all the tested domains (masticatory function, psychological discomfort, social disability, pain and oral hygiene). Better results were achieved using a silicone-based soft liner, which recommends it as the material of choice for relining dentures.